Inter-Group Variation in Non-Conceptive Sexual Activity in Female Japanese Macaques: Could it be Cultural? - Jean-Baptiste Leca (Animal Behavior and Cognition, 2014)
We compared two non-conceptive sexual behavioral patterns (female-male mounting – FMM – and female-female mounting – FFM) across four free-ranging groups of Japanese macaques (Macaca fuscata) living at three different field sites in Japan (Arashiyama, Minoo, and Jigokudani). We found marked inter-group differences and covariation in the frequency and form of FMM and FFM. This result supports the view that FMM and FFM in Japanese macaques are developmentally and evolutionarily linked. The customary occurrence, high prevalence, and great diversity of FMM and FFM at Arashiyama may be the result of combined favorable socio-demographic conditions, namely few resident males, most of them being old, sexually under-motivated, and less aggressive and controlling than the average male Japanese macaques. We suggest that FMM and FFM may be cultural sexual practices in the Arashiyama-E group. In most other populations, all the aforementioned favorable socio-demographic conditions are not met, and although female mounting may occasionally be expressed by several group members, it does not reach the group-level tradition status. Our cultural interpretation of female mounting in Japanese macaques is consistent with evidence of the social transmission of courtship behaviors and mating preferences in various animal taxa, including nonhuman primates and humans. Our study may have implications for the evolution of non-conceptive sexuality in humans, including sexual fluidity in women.